The challenge of individuality in Cultural-Historical Activity Theory: “collectividual” dialectics from a transformative activist stance (Práxis Educativa, 2022)
In addressing the persistent challenge of fully integrating individual dimensions and human subjectivity within the cultural-historical activity theory, this paper suggests several steps to revise its core onto-epistemology in an expansive approach termed the transformative activist stance. This approach outlines the subtle dialectics of individual and collective planes of human praxis whereby each individual is shaped by collective history and collaborative practices while at the same time shaping and realizing them through contributing to their collective, dynamic materiality in moving beyond the status quo. In capitalizing on people always transcending what exists in ‘the here and now,’ in a non-adaptive fashion, based in a commitment and vision to how the world “ought to be,” the individual subjectivity is reclaimed as itself a fully social, embodied, material-discursive process. Individual subjectivity and agency gain status through contributing to changes in “collectividual” practices as the primary onto-epistemology of a unitary realm that is individual and social/collective at the same time.Keywords: Individual/social. Dialectics. Praxis. Transformative Activist Stance.